Validation of diagnostic accuracy using digital slides in routine histopathology - Fónyad László; Krenács Tibor; Nagy Péter; Zalatnai Attila; Csomor Judit; Sápi Zoltán; Pápay Judit; Schönléber Júlia; Diczházi Csaba; Molnár Béla (BMC, 2012)
Abstract Background Robust hardware and software tools have been developed in digital microscopy during the past years for pathologists. Reports have been advocated the reliability of digital slides in routine diagnostics. We have designed a retrospective, comparative study to evaluate the scanning properties and digital slide based diagnostic accuracy. Methods 8 pathologists reevaluated 306 randomly selected cases from our archives. The slides were scanned with a 20× Plan-Apochromat objective, using a 3-chip Hitachi camera, resulting 0.465 μm/pixel resolution. Slide management was supported with dedicated Data Base and Viewer software tools. Pathologists used their office PCs for evaluation and reached the digital slides via intranet connection. The diagnostic coherency and uncertainty related to digital slides and scanning quality were analyzed. Results Good to excellent image quality of slides was recorded in 96%. In half of the critical 61 digital slides, poor image quality was related to section folds or floatings. In 88.2% of the studied cases the digital diagnoses were in full agreement with the consensus. Out of the overall 36 incoherent cases, 7 (2.3%) were graded relevant without any recorded uncertainty by the pathologist. Excluding the non-field specific cases from each pathologist's record this ratio was 1.76% of all cases. Conclusions Our results revealed that: 1) digital slide based histopathological diagnoses can be highly coherent with those using optical microscopy; 2) the competency of pathologists is a factor more important than the quality of digital slide; 3) poor digital slide quality do not endanger patient safety as these errors are recognizable by the pathologist and further actions for correction could be taken. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1913324336747310.